Genome-wide association study identifies three novel genetic markers associated with elite endurance performance - Ahmetov, I. I.; Kulemin, N. A.; Popov, D. V.; Naumov, V. A.; Akimov, E. B.; Bravy, Y. R.; Egorova, E. S.; Galeeva, A. A.; Generozov, E. V.; Kostryukova, E. S.; Larin, A. K.; Mustafina, L. J.; et al. (Biology of Sport, 2015)
To investigate the association between multiple single-nucleotide polymorphisms (SNPs), aerobic performance and elite endurance athlete status in Russians. By using GWAS approach, we examined the association between 1,140,419 SNPs and relative maximal oxygen consumption rate ( ·VO2max) in 80 international-level Russian endurance athletes (46 males and 34 females). To validate obtained results, we further performed case-control studies by comparing the frequencies of the most significant SNPs (with P<10-5-10-8) between 218 endurance athletes and opposite cohorts (192 Russian controls, 1367 European controls, and 230 Russian power athletes). Initially, six `endurance alleles` were identified showing discrete associations with ·VO2max both in males and females. Next, case-control studies resulted in remaining three SNPs (NFIA-AS2 rs1572312, TSHR rs7144481, RBFOX1 rs7191721) associated with endurance athlete status. The C allele of the most significant SNP, rs1572312, was associated with high values of ·VO2max (males: P=0.0051; females: P=0.0005). Furthermore, the frequency of the rs1572312 C allele was significantly higher in elite endurance athletes (95.5%) in comparison with non-elite endurance athletes (89.8%, P=0.0257), Russian (88.8%, P=0.007) and European (90.6%, P=0.0197) controls and power athletes (86.2%, P=0.0005). The rs1572312 SNP is located on the nuclear factor I A antisense RNA 2 (NFIA-AS2) gene which is supposed to regulate the expression of the NFIA gene (encodes transcription factor involved in activation of erythropoiesis and repression of the granulopoiesis). Our data show that the NFIA-AS2 rs1572312, TSHR rs7144481 and RBFOX1 rs7191721 polymorphisms are associated with aerobic performance and elite endurance athlete status.